Digital Marketing and Pedagogical Competencies: Business Educators‘ Perspectives on Graduate Employability in Southeast Nigeria - Ifeoma I. Ekwealor; Constance I. Okoli (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The increasing shift to digital channels in business has led to a growing need among businesses for employees to be proficient in digital marketing, and educators, to have digital pedagogical skills to train such employees. This study investigated business educators' perceptions of the digital marketing and digital pedagogical skills equipments needed for the employment of business education graduates in Anambra state of Nigeria. The design of the study employed was a descriptive survey which was based on 45 business educators who answered a validated questionnaire. The mean, SD and ANOVA were used to analyze the data. The results showed that employability of graduates was very much in need of digital marketing and digital pedagogical skills. In addition, there were no gender or experienced teachers differences in the respondents' ratings. From this study, it is recommended that structured professional development programmes for teachers should be developed to be provided to teachers to gain knowledge on digital teaching technologies and, digital marketing experiences should be integrated to the business education programme.